2011
DOI: 10.1007/s13595-011-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mechanically perturbed young stems: can it be used for wood quality screening?

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Trees were grown for eight months, at which point they had reached a height of approximately 80 cm. Trees were grown upright, tilted by staking at 45°from the vertical, or rocked in a purpose-built frame for 15 min in every hour at a rate of 24 cycles/min, reaching 22°from the vertical; this rocking began after 2 months and continued for a further six months (Apiolaza et al 2011). In this way four different corewoods were produced: 'normal' corewood, opposite corewood, compression corewood, and flexure corewood.…”
Section: Wood Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trees were grown for eight months, at which point they had reached a height of approximately 80 cm. Trees were grown upright, tilted by staking at 45°from the vertical, or rocked in a purpose-built frame for 15 min in every hour at a rate of 24 cycles/min, reaching 22°from the vertical; this rocking began after 2 months and continued for a further six months (Apiolaza et al 2011). In this way four different corewoods were produced: 'normal' corewood, opposite corewood, compression corewood, and flexure corewood.…”
Section: Wood Materialsmentioning
confidence: 99%
“…Wood formed in trees that do not have uneven maturation stresses is often referred to as normal wood for the purposes of comparing with wood formed under mechanical stress. Another type of wood, flexure wood, is produced by trees that are subjected to extensive mechanical flexing (e.g., by wind), allowing trees to assume a higher curvature without damage (Telewski and Jaffe 1986a, b;Telewski 1995;Cordero 1999;Pruyn et al 2000;Mickovski and Ennos 2003;Kern et al 2005;Apiolaza et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies which have used acoustics to obtain stiffness measurements on juvenile trees include references. 12,44,143,144,160,177,213,[256][257][258][259][260][261][262][263][264][265][266][267] Many of these have investigated the effect of stress such as tilting or drought. Investigations using acoustic velocity for more mature juvenile trees include references.…”
mentioning
confidence: 99%
“…During drought stress, cambium enters a semi-dormant state, which inhibits cell division and stem growth (Shepherd 1964). There were no significant differences in growth between leaned and straight young P. radiata plants (Apiolaza et al 2011a). Similarly, there was no significant difference in growth between staked and the unstaked plants ).…”
Section: Growth and Biomassmentioning
confidence: 75%
“…CW in vertical stems results from corrections to a previous leaning or from small, less obvious asymmetric loadings within the stem. Occurrence of 13-17% CW in rocked and straight plants has been reported (Apiolaza et al 2011a), apparently caused by the stem movement. Several studies have suggested that the formation of CW aids stems to remain straight, and can be prevalent even in straight trees (Warensjö and Rune 2004).…”
Section: Compression Wood (Cw)mentioning
confidence: 99%